Specific Expression of a New Bruton Tyrosine Kinase Isoform (p65BTK) in the Glioblastoma Gemistocytic Histotype - Sala, Luca; Cirillo, Giovanni; Riva, Gabriele; Romano, Gabriele; Giussani, Carlo; Cialdella, Annamaria; Todisco, Antonio; Virtuoso, Assunta; Cerrito, Maria Grazia; Bentivegna, Angela; Grassilli, Emanuela; Ardizzoia, Antonio; et al. (Frontiers in Molecular Neuroscience, 2019)
Bruton’s tyrosine-kinase (BTK) is a non-receptor tyrosine kinase recently associated with glioma tumorigenesis and a novel prognostic marker for poor survival in patients with glioma. The p65BTK is a novel BTK isoform involved in different pathways of drug resistance of solid tumors, thus we aimed to investigate the expression and the putative role of p65BTK in tumors of the central nervous system (CNS). We selected a large cohort of patients with glial tumors (n=71) and analyzed the expression of p65BTK in different histotypes and correlation with clinical parameters. Sections were stained with glial fibrillary acidic protein (GFAP), p53, epidermal growth factor receptor (EGFR), S100, vimentin, and epithelial membrane antigen (EMA) antibodies. Glioma stem cell (GSC) lines, isolated from glioblastoma multiforme (GBM), were treated with different concentrations of ibrutinib, a specific inhibitor of BTK, in order to evaluate their metabolic activity, mitotic index and mortality. Moreover, an orthotopic xenotransplant of GSC from human GBM was used to evaluate the expression of p65BTK in the brain of immunodeficient mice. p65BTK was expressed in GSC and in gemistocytes in human gliomas at different histological grade. We found a significant correlation between BTK expression and low-grade tumors (p≤0.05) and overall survival of patients with grade III gliomas (p≤0.05), suggestive of worst prognosis. Interestingly, the expression of p65BTK remained restricted exclusively to gemistocytic cells in the xenograft mouse model. Ibrutinib administration significantly reduced metabolic activity and mitotic index and increased mortality in GSC, highlighting the specific role of p65BTK in cell proliferation and survival. In conclusion, our data demonstrated that p65BTK is expressed in glioma tumors, restricted to gemistocytic cells, has a key role in GSC and has a bad prognostic value, thus highlighting the importance of future research for targeted therapy of human gliomas.